Transformasi digital dan strategi keuangan syariah dalam memaksimalkan peluang pasar - Audyzza, Keysa Fahradine (Maliki Interdisciplinary Journal, 2024)
This journal discusses digital transformation in Islamic financial institutions (IFIs) and the strategies needed to maximize market opportunities in the era of the industrial revolution 4.0. Digital transformation involves not only the application of technology, but also changes in culture, processes, and business strategies that support sharia principles. With the increased use of technology, LKS can improve operational efficiency, expand access to financial services, and ensure compliance with Islamic law. In addition, digitalization allows the public, including the millennial generation, to access Islamic financial products and services more easily. However, challenges such as data security and sharia compliance remain to be faced. Through the utilization of artificial intelligence and data analytics, LKS can understand customer behavior and identify market trends, thereby improving service personalization and smarter decision-making. This journal highlights the importance of a comprehensive strategy in implementing digital transformation to achieve success in the Islamic finance industry.